PARTISIPASI PEREMPUAN DALAM PEMANFAATAN ENERGI TERBAHARUKAN DI PEDESAAN - Abubakar Lubis (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
The renewable energy generally can support or trigger the economic growth in household utilization, and give rise to the opportunity for people (men or women) in rural areas to run small scale home industry. The introduction of renewable energy in rural areas will significantly transform the social, cultural and economic structure from traditional style to modern (western) one. The structural transformation will force all people to be drawn in. Many benefits can be gained if women participate in the transformation.This paper describes the impacts which will take place during the structural transformation in rural areas, in general, and women participation in particular. This will greatly determine the accomplishment in the policy and implementation of technology adaptation in renewable energy field.